Diagnostic Significance of Intracystic Nodules on MRI in Rathke’s Cleft Cyst - Shou-sen Wang; De-yong Xiao; Ying-hao Yu; Jun-jie Jing; Lin Zhao; Ru-mi Wang (International Journal of Endocrinology)
Background and Purpose. To explore strategies for the diagnosis and treatment of Rathke’s cleft cyst (RCC). Methods. The medical records of 24 patients with sellar RCC were retrospectively reviewed. Two patients had concomitant pituitary adenoma, 2 underwent transcranial surgery, and 22 underwent transsphenoidal surgery. The clinical features, especially the findings of intracystic nodules on MRI, were evaluated and compared with the pathological findings. Results. Preoperatively, only 2 patients were diagnosed with RCC or suspected RCC. Pre- and postoperative MRI images revealed 10 intracystic nodules in 9 (37.5%) patients. Two nodules had bull's eyelike changes. The signal intensity of the intracystic nodules varied on T1- and T2-weighted images. Not all nodules on T2-weighted images were visualized. Postoperative MRI revealed recurrence or residual lesion in 5 patients; none had new symptoms and a second surgery was not required. Conclusions. Identifying intracystic nodules is important in patients with sellar cystic lesions. Bull’s eyelike change in an intracystic nodule on MRI, which is reported here for the first time, potentially might have value for confirming the diagnosis.